Integrating Reservoir Properties with Microfacies Analysis of the Mishrif Formation at Zubair Oilfield, Iraq - Al-Najm, Fahad M.; Al-Samer, Heba A.; Shehab, Mayssa N.; Mahdi, Maher M. (Iraqi Journal of Science, 2025)
Six wells were selected in this study for the Mishrif Formation (Late Cenomanian - Early Turonian) in the Zubair oilfield in southern Iraq, which is considered one of the main reservoirs in the field, to study the microfacies and to evaluate the petrophysical properties. This study estimates shale volume, distribution (dispersed, laminar and structural), and formation effective porosity from well log data and cross-plots. The distribution of shale is mainly dispersed,and an increase in effective porosity values indicates the quality of the reservoir. The microfacies analysis and the Lucia plot demonstrate that the Mishrif Formation consists of four main Microfacies (Lime mudstone, Wackestone, Packstone and Grainstone) in wells Zb-40 and Zb-114 containing only the core. The logs interpretation shows that the Mishrif Formation consists mainly of clean limestone rocks. The composition was divided based on the qualitative and quantitative interpretation of the logs into three reservoir units (MA, MB1, MB2). MB2 was divided into MB2.1 and MB2.2 based on oil and water saturation ratio. The results of the petrophysical analysis showed that MB1 and MB2.1 were the best reservoir units in terms of oil saturation and porosity in the study wells.